Comparison of technologies to control the physiological, biochemical and nutritional changes of fresh cut fruit - Baeza, Rita (Kansas State University, 2007)
Fresh cut fruits are products with minimal processing, modified by cutting, washing, packaging and refrigeration. The objective of this review is to present an overview of the available technologies for processing fresh cut fruits and technologies that could have some potential to be used in the future due to the increased consumption of fresh cut fruits. Fresh cut products are ready to eat, have high moisture content, have lack of lethal step to eliminate microbial pathogens and have the potential for temperature abuse; all these factors make quality and safety a priority. Fresh cut products sales have increased as a consequence of increased consumption of fruits and consumer attitudes toward convenience. Fresh cut fruit differ from fresh fruits in that the tissue and cell integrity have may been disrupted resulting in consequences such as changes in ethylene production, respiration, membrane degradation, metabolite accumulation, water loss and microba spoilage. However, the response to cutting depends on other variables such as cultivars, maturity and raw material quality, shape of cut, sharpness of blade, temperature and atmospheric composition. Consequently, there are enzymatic changes that impact the shelf life and quality of these products. In addition to quality and safety the nutritional value is an important factor too because consumers demand products as close to fresh as possible. The evaluation of the nutrient losses and how to reduce them through different treatments such as the introduction of vitamins and minerals in coating treatments or other treatment has become a priority too. There is a real need to find alternatives for preservation of fresh-cut fruit in order to minimize the changes that occur in the fruit tissues as a consequence of wounding. Alternatives, combined or modified methods have been proposed such as the use of alternative antibrowning, ethylene scrubbing, heat treatments, alternative antimicrobials, alternative packaging films, vacuum impregnation, osmotic dehydration, high hydrostatic pressure, use of edible coatings, radiation, bio preservation and other technologies.
Keywords: fresh cut fruit treatments; Agriculture, Food Science and Technology (0359)